2016
DOI: 10.1371/journal.pone.0148693
|View full text |Cite
|
Sign up to set email alerts
|

Luteoloside Acts as 3C Protease Inhibitor of Enterovirus 71 In Vitro

Abstract: Luteoloside is a member of the flavonoids family that exhibits several bioactivities including anti-microbial and anti-cancer activities. However, the antiviral activity of luteoloside against enterovirus 71 (EV71) and the potential mechanism(s) responsible for this effect remain unknown. In this study, the antiviral potency of luteoloside against EV71 and its inhibitory effects on 3C protease activity were evaluated. First, we investigated the cytotoxicity of luteoloside against rhabdomyosarcoma (RD) cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 49 publications
(63 reference statements)
0
28
0
Order By: Relevance
“…Many studies have shown that flavonoids may protect cardiomyocytes against I/R injury (Yuan et al, ; Zhang et al, ). Lut, a flavonoid compound extracted from honeysuckle, exhibits anti‐inflammatory, antiviral, and anticancer properties (Cao et al, ; Hwang, Lee, Kim, & Hwang, ; Jung, Jin, Min, Kim, & Choi, ; Tian et al, ) and has shown promising results in myocardial cells. A/R injury was used to model I/R injury in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that flavonoids may protect cardiomyocytes against I/R injury (Yuan et al, ; Zhang et al, ). Lut, a flavonoid compound extracted from honeysuckle, exhibits anti‐inflammatory, antiviral, and anticancer properties (Cao et al, ; Hwang, Lee, Kim, & Hwang, ; Jung, Jin, Min, Kim, & Choi, ; Tian et al, ) and has shown promising results in myocardial cells. A/R injury was used to model I/R injury in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis was performed as previously described 9 , 66 , 67 . Briefly, Vero cells (1 × 10 6 cells/well) seeded into 6-well plates were infected with EV71 (100 TCID 50 ) at 37 °C for 2 h. After removing the virus, the infected cells were treated with 100 µM ICAC.…”
Section: Methodsmentioning
confidence: 99%
“…5 Luteolin has considerable pharmacological value, including antitumor, antioxidative, neuroprotective, and anti-inflammatory effects. [6][7][8][9] The anticancer effect of luteolin has been investigated in various cancers. [10][11][12][13][14][15] For example, luteolin inhibited the proliferation of human cholangiocarcinoma cells by inducing apoptosis and interrupting OncoTargets and Therapy 2019:12 submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%